PENGARUH MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI KARYAWAN MAGANG BAKTI BCA PADA PT. BANK CENTRAL ASIA TBK. KANTOR CABANG UTAMA JAMBI - Sakinah As; Firdaus Warbyal Ilham (Universitas Batanghari, 2018)
The research aims to analyze the influence of work motivationon organizational commitment. This research is done on Bakti BCA internship employee who work as teller and customer services of PT. Bank Central Asia Tbk.main branch office of Jambi amounted at 60 people. Technique used in sampling is census, where all of the population is used as sample. Analysis unit used is simple linear regression. The research result that work motivation influence positively and significantly on organizational commitment.